Pengaruh Work Life Balance terhadap Stres Kerja pada Guru Perempuan yang Telah Berkeluarga di Kecamatan Koto Tangah - Rinjani, Azzahra Putri; Rinaldi, Rinaldi (Lembaga Yasin AlSys, 2024)
The purpose of this study is to see the effect of work life balance on work stress on female teachers who have a family in Koto Tangah District. This study uses purposive sampling techniques, determining samples with certain considerations. The subject of this study was 110 teachers. The data collection method in this study uses the work life balance scale and work stress. Data is processed by using simple regression analysis. Hypothesis test results with a significance value (p-value) of 0.000, indicate that the effect of the work life balance variable on work stress variables is very significant. While the negative regression coefficient of -0,724 in this study shows that each increase in work life balance will reduce the level of work stress by 0.724. The correlation coefficient (R) of 0.525 shows a positive linear relationship between work life balance and work stress.